Benign white lesions of the oral mucosa: clinical presentation, diagnosis and treatment (Research, Society and Development, 2021)
Benign white lesions in the oral cavity have high recurrence and represent a group of entities whose main clinical manifestation is the presence of white areas in the mouth. Although there are classic features associated with each lesion, clinical appearances can be confounded, leading to incorrect diagnosis and treatment. Given the above, this work aims to describe the most common benign white lesions found in the oral mucosa, highlighting their etiology, clinical presentation, diagnosis and treatment. For the construction of this work, a bibliographic survey was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect databases, using the Mendeley reference manager. From the narrative review of the literature, it was observed that the most recurrent benign white lesions affecting the oral mucosa are pseudomembranous candidiasis, leukoplakia, nicotinic stomatitis, actinic cheilitis, leukoedema, lichen planus, lichenoid contact reaction, nibbling injury, line alba and white spongy nevus. Therefore, it is extremely important that health professionals are familiar with these lesions, distinguishing them from malignant lesions that affect the cavity, in order to establish the correct treatment for each case.